Formation of the tax control mechanism under application of transfer pricing conditions in the Republic of Tajikistan - Sidikovich, Shokirov Ravshan; Khasanovich, Ismatov Khushruz (International Journal of Psychosocial Rehabilitation, 2020)
Under the global conditions of the main streamline towards economical interaction of state is considered to be tax regulation of transfer pricing, it`s directly connected with changed budget potential of the country. In conformity with the author’s opinions, the mechanism of tax regulation beset with transfer pricing in Tajikistan Republic is mostly manifested towards the development of internationalization of production and in the relevant streamlines there are a large considerable number of factors that should be taken into account in the implementation of tax policy as well.Tax regulation of transfer pricing is becoming an important area of a state economic interaction in the context of globalization. It is directly related to changes in the country's budget potential. The mechanism of tax regulation of transfer pricing in the Republic of Tajikistan, which has not yet been formed, is largely manifested in the development of internationalization of production and, in this direction, there are a number of factors that should be taken into account in the implementation of tax policy.From the perspective of the study in this direction the main scientific results were obtained, which include: justification of an adequate mechanism of tax control of transfer pricing in the conditions of the Republic of Tajikistan; development of proposals for the adoption of the regulatory and legal framework of the Republic of Tajikistan in the field of tax regulation of transfer pricing.